Elephant dung as potting medium for root trainer plants of rubber - Thomas V; George S (PLACROSYM XXI. International Symposium on Plantation Crops, 10-12 December 2014, Kozhikode, India, pp. 99-100. Abstracts.)
The nursery practices in rubber industry have been revolutionalised with the recent introduction of root trainer plants grown in containers with soilless media. After seasoning for 2-3 months, coir pith is used as potting medium in root trainer cups. Apart from certain advantages, presence of high amount of phenolic contents, lebgthy pretreatment, less nutritive value, availability restricted to coastal areas are some of the limitations attributed for coir pith to be used as potting medium for rubber (Hevea brasiliensis). Partially dried elephant dung was tried as an alternative to coir pith alone or in combination with coir pith or soil to fill the root trainer cups. Planting was carried out with brown budded stumps. Prophylactic measures for fungus and termites were taken timely. Watering was carried out in alternative days. Fertilizer application was carried out as per current recommendations for root trainer (RT) cups. Periodic observations on bud sprouting success, length and diameter of the shoot, number of leaf whorls and leaves per whorl were recorded. Among the treatments, plants grown in elephant dung in combination, with soil showed superiority for early bud sprouting, shoot length and its diameter, and number of leaf whorls over other potting medium. Shoot length, diameter and number of leaf whorls recorded higher values for elephant dung + soil (44.34 cm, 6.8 mm and 1.6, respectively) followed by elephant dung + soil + coir pith (38.13, 6.44 and 1.52) and the least values were recorded for elephant dung alone (32.17, 5.77 and 1.2). As an underutilized fibrous animal excreta that causes serious environmental and economical andconcern, how best the elephant dung can be utilized in rubber nurseries as an alternative potting medium to coir pith is discussed.
Keywords: Elephant dung; Potting medium; Root trainer